Psycholosexual Disorders in Women of Reproductive Age - Mustafa, Hira; Yasmen, Farkhana; Memon, Saira Parveen; Ghumro, Rashida; Rafique, Madiha; Mahar, Saifullah (Indus Journal of Bioscience Research, 2025)
Background: Psychosexual disorders significantly impact the overall well-being of women of reproductive age, yet they remain underdiagnosed and undertreated. This study aimed to assess the prevalence, predictors, and mental health associations of psychosexual disorders in women of reproductive age. Methodology: A cross-sectional study was conducted on a cohort of women, evaluating demographic, clinical, and psychological factors influencing psychosexual health at the Department of Gynaecology and Obstetrics of PUMHSW, for the duration of six months from March 2024 to August 2024. Standardized diagnostic criteria and validated assessment tools were employed to categorize psychosexual disorders, while statistical analyses, including chi-square tests and logistic regression, were performed to determine associations and predictors. Results: A high prevalence of psychosexual dysfunction was observed, with desire and arousal disorders being the most frequent. Depression and anxiety were significantly associated with reduced sexual function, and advancing age and chronic illnesses further exacerbated the condition. Regression analysis confirmed mental health conditions as strong predictors of psychosexual disorders. Conclusion: The study underscores the strong interconnection between psychosexual dysfunction and psychological health, emphasizing the need for an integrated, multidisciplinary approach to diagnosis and management. Future research should focus on targeted interventions to improve sexual well-being in affected women.